"Can you tell me why you made that choice?": A qualitative study of the influences on treatment decisions in advance care planning among adolescents and young adults undergoing bone marrow transplant. (March 2020) - Needle, Jennifer S; Peden-McAlpine, Cynthia; Liaschenko, Joan; Koschmann, Kara; Sanders, Noah; Smith, Angela; Schellinger, Sandra E; Lyon, Maureen E
Background: Adolescent and young adult advance care planning is beneficial in improving communication between patients, surrogates, and clinicians. The influences on treatment decisions among adolescents and young adults are underexplored in the literature. Aim: The aim of this study was to explore and better understand the influences on decision-making for adolescent and young adult bone marrow transplant patients about future medical care. Design: Clinical case studies and qualitative inductive content analysis of treatment decisions made during the Respecting Choices ® Next Steps Pediatric Advance Care Planning conversation as a component of the Family-Centered Advance Care Planning Intervention. Settings/participants: A total of 10 adolescent and young adult patients (aged 14–27 years) undergoing bone marrow transplant at an academic Midwest children's hospital were involved in the study. Results: Influences on participants' decisions were consideration for family, quality of life, and awareness of self. Desire to avoid suffering and maintain an acceptable quality of life was often in competition with participant's concern over the perceived negative impact of discontinuing treatment on their families. Conclusion: This study highlights that adolescent and young adult bone marrow transplant patients are capable of meaningful deliberation about future treatment decisions. Influences on decision-making should be incorporated into advance care planning conversations to facilitate communication between patients and their surrogates. Longitudinal research is needed to explore these influences throughout the trajectory of illness.